2010
DOI: 10.1007/s10493-010-9413-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation and reproductive incompatibility of three coconut-mite-associated populations of predatory mites identified as Neoseiulus paspalivorus (Acari: Phytoseiidae)

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
2
5
0
4
Order By: Relevance
“…In addition to genetic differences observed, the cross-breeding experiments showed that populations studied represent distinct biological entities (Biological species, sensu Mayr 1940), as has been observed for several phytoseiid and phytophagous mite species (McMurtry et al 1976;Mahr and McMurtry 1979;Monetti and Croft 1997;Noronha and Moraes 2004;Klimov et al 2004;Famah Sourassou et al 2011). There are several explanations for the absence of offspring in crosses between populations.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to genetic differences observed, the cross-breeding experiments showed that populations studied represent distinct biological entities (Biological species, sensu Mayr 1940), as has been observed for several phytoseiid and phytophagous mite species (McMurtry et al 1976;Mahr and McMurtry 1979;Monetti and Croft 1997;Noronha and Moraes 2004;Klimov et al 2004;Famah Sourassou et al 2011). There are several explanations for the absence of offspring in crosses between populations.…”
Section: Discussionmentioning
confidence: 64%
“…Famah Sourassou et al (2011) performed multivariate morphometric analysis and crossing experiments with three populations of N. paspalivorus (Benin, Ghana and Brazil) and concluded that the studied populations were different species, despite their morphological similarity. Famah Sourassou et al (2012) used multivariate morphometric analysis, molecular analyses and crossing experiments with populations of N. baraki from Benin, Tanzania and Brazil.…”
mentioning
confidence: 99%
“…Diferenças biológicas têm sido observadas não apenas entre espécies claramente distintas, mas mesmo entre espécies muito próximas e entre populações distintas de uma mesma espécie (OKASSA et al, 2009;SOURASSOU et al, 2011).…”
Section: Respectivamenteunclassified
“…A variação de parâmetros morfológicos entre populações de fitoseídeos tem sido citada na literatura (NORONHA; MORAES, 2002;OKASSA et al, 2009;SOURASSOU et al, 2011). Embora variações dessas características entre indivíduos de uma espécie de fitoseídeo sempre existam, o intervalo de variação de cada estrutura é usualmente desconhecida.…”
Section: Respectivamenteunclassified
See 1 more Smart Citation